An experimental investigation on black liquor combustion in fluidized and spouted bed reactors - Madrazo, Alma Bella P.
A study was conducted to design and fabricate a laboratory scale model of a fluidized bed combustor which is converible to a spouted mode which will be used to determine the suitability of the fluidized bed combustion process to burn weak black liquor ( 12% solids content), and strong black liquor (42% solids content) and establish its optimum operating conditions. The black liquor was supplemented with charcoal fines in the following mixture specifications: 10% charcoal -90% black liquor, 20% charcoal -80% black liquor and both were tested in the spouted bed and fluidized (perforated) bed using an average of 53.84 g. of back up charcoal fines to enhance combustion. Based on the data obtained, the 20% charcoal - 80% strong black liquor mixture at 140 1/min air flowrate using a spouted bed gave the best fit that established the linear relationship between the feed rate and the bed temperature. Using the perforated bed, data indicated that the 20% charcoal - 80% strong black liquor mixture gave the best results. The optimum performance of the fluidized bed combustor both for spouted and perforated beds was found to be at a bed temperature range of 550̊̊C - 750̊̊C. At these temperature ranges, only very minimal CO is produced. At optimum operating conditions the combustion efficiency for both types of bed ranges from 94% to 99%. The results clearly indicate that the spouted and fluidized bed combustor is a suitable equipment for black liquor combustion. Fluidized bed combustion technology therefore is a good alternative thermal recovery process for small pupl mills.